PENYULUHAN DAN PENDAMPINGAN TEKNOLOGI PENGENDALIAN OPT TANAMAN PADI PADA KELOMPOK TANI DI DESA CIDAHU - KEC. PASAWAHAN – KAB. KUNINGAN - Deden, Deden; Heryanto, Yanto (Jurnal Pintar Abdimas, 2021)
OPT attack on rice plants is a serious threat that can reduce the potential yield of agricultural products so that production is unstable and tends to decline. By knowing the causative factors, we can create a control strategy by selecting and applying technical technical steps and pesticide analysis as pest control that is environmentally sound and has a high level of efficiency. PKM activities are carried out in Cidahu Village - Pasawahan District - Kuningan Regency, from July to November 2021. The purpose of this service activity is to increase knowledge and understanding of the community, especially farmer groups about strengthening farmer group institutions and pest control technology in rice plants. Counseling is carried out using extension methods and demonstration plots. Measurement of the success rate of PKM through Pre-test and Post-test to all participants. The data were analyzed using the Quasi-experimental method. PKM results showed that PKM activities were able to increase farmers' knowledge about pest control technology in rice plants. The results of the PKM activity increased the maximum knowledge score of farmers by 12 points from before and the minimum knowledge score rose to 16 points from the previous. PKM activities provide equitable knowledge skills for PKM participating farmers, as evidenced by the percentage result value of the coefficient of variation of participants being lower than the coefficient of variation before the PKM was implemented.